ANALISIS STRUKTUR PADA GIRDER OVERHEAD CRANE SWL 30 TON - Jefriansyah Jefriansyah; Ma'ruf Ma'ruf (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2018)
Overhead crane is a device used to move goods. Overhead cranes are very important during the production period, if there is a problem in the overhead crane, it can disrupt the production process. Therefore, load testing was conducted to determine the results of the girder deflection, whether large deflection is still within the limits that are allowed or not. This study to calculate the girder overhead crane occur in the loading variations, and adjust the properties of the material used. The amount of deflection is calculated using the equation Castigliano theory. research on the loading of 28.7 tons, 30 tons, and 37.5 tons with theoretical calculations obtained deflection value calculation results is 6,060mm, 6,335mm, and 7.918 for the imposition of the middle girder (1 / 2span). 5,191mm, 5,410mm and 6,763mm for the loading side (1 / 3span). The simulation results are 5,649mm, 5,834mm, and 6.898 for the imposition of the middle girder (1 / 2span) and 4,986mm, 5,101mm and 6,032mm for the loading side (1 / 3span). The results obtained have great value below allowable deflection value is 23.75 mm.